FAKTOR PENGARUH CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PENGGUNA ONLINE FOOD DI JAKARTA - Ridho Pratama Refdi; Mohamad Rizan; Ika Febrilia (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study is to find out whether brand image, e-service quality, has an effect on customer loyalty with customer satisfaction as an intervening variable for online food users in Jakarta. This study used a sample of 200 respondents. Data collection was carried out by distributing a questionnaire survey to 200 customer respondents who had used online food ordering services Grab Food, Go-Food, or Shopee Food at least 3 times, with sampling locations in Jakarta. Data processing was carried out using the SEM method. The results of this study indicate that brand image and e-service quality have a positive and significant effect on customer satisfaction. Brand image and electronic service quality have a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. Brand image affects customer loyalty indirectly which is the influence of customer satisfaction as an intervening variable. Electronic service quality affects customer loyalty indirectly which is the influence of customer satisfaction as an intervening variable